Chronic nodules of sigmoid perforation caused by incarcerated intrauterine contraception device. Issue 4 (January 2019) - Huang, Xiaohui; Zhong, Rui; Zeng, Liqin; He, Xuhui; Deng, Qingshan; Peng, Xiuhong; Li, Jieming; Luo, Xiping
Abstract: Rationale: It is extremely rare for an intrauterine contraception device (IUD) to cause uterine perforation and Sigmoid perforation for a long time without being detected. Patient concerns: We present a case of a patient who has suffered from abdominal pain after 4 years of placement of an IUD, and found that the IUD was incarcerated by ultrasound. Diagnoses: Laparoscopic and hysteroscopic examination revealed that the incarcerated IUD caused uterine perforation and sigmoid perforation for a long time. One end of the intrauterine device completely penetrated the anterior wall muscle layer of the uterus and the full layer of the sigmoid colon, located in the intestinal lumen, and the perforated portion of the sigmoid colon formed a chronic nodule. Interventions: We extended the sigmoid colon perforation and uterine perforation by laparoscopy, removed the incarcerated IUD from the uterus through the vagina, trimmed the chronic nodules of the sigmoid perforation, repaired the sigmoid colon, and repaired the uterine perforation. Outcomes: The patient was cured and discharged 22 days after surgery. The patient was naturally pregnant 3 months after surgery and delivered by cesarean section 12 months after surgery. We saw a good recovery of the uterus and sigmoid colon during cesarean section. Lessons: The patient was placed with an intrauterine device made of a special material and was not monitored after placement, causing the uterus and sigmoid perforation to be undetected for a long time. The IUD placed in the patient should be monitored regularly. If the IUD is found to be incarcerated or displaced, attention should be paid to uterine perforation and intestinal perforation.